LONG TERM SHARE PRICE PERFORMANCE OF COMPANIES POST MERGERS AND ACQUISITIONS - D'souza, Nita (2006)
A study of 29 mergers and acquisitions of UK targets during the period 1998-2000 was undertaken to examine the post acquisition returns of acquirers in the long-term by assessing the extent to which share price performance was abnormal. The acquirers were based in US, Europe and Africa. The Buy and Hold Abnormal Return (BHAR) methodology was adopted and benchmark industries were selected as per the size-adjusted model, where size was the market value of the bidder. It was observed that 18 out of the 29 companies in the sample underperformed in the 3-year post merger period having BHARs in the range of -2% to -98%. Additionally, 18 out the 28 bids that were amicable had BHARs between -3% to -98% and tended to underperform on an average. However, the results did not support the means of payment hypothesis and 14 out of the 21 companies that used cash as method of financing the acquisitions had negative performance of -41.91%, on an average.